Model of X-ray polycapillary lens in the geometrical optics approximation; Bulletin of the Lebedev Physics Institute; Vol. 45, iss. 12 - Uglov S. R. Sergey Romanovich; Filatov N. A. Nikolay Alexandrovich; Chistyakov S. G. Sergey Gennadevich; Gogolev A. S. Aleksey Sergeevich; Kazaryan M. A. Mishik Ayrazatovich; Obkhodskiy A. V. Artem Viktorovich (2018, 2018)
Title screen